Forms, methods and means of studying its pedagogical capabilities through the use of the Uzbek national spiritual heritage in the activation of Primary School students. - Toshtemirova Maftuna Tolibjonova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
It is also desirable to carry out its pedagogical capabilities not only in the course process, but also in an integral way with the extracurricular educational process, through the use of the Uzbek national and spiritual heritage in the activation of Primary School students.